TOXICIDADE DE NANOTUBOS DE CARBONO FUNCIONALIZADOS E NÃO FUNCIONALIZADOS IN VITRO - Menezes, Patrick Flôres (2016)
Carbon nanotubes (CNT) are structures of a few centimeters in length, and with a nanometer radius. The application of CNT has been diverse, from nanosensors to drug carriers, and therefore its toxicological evaluation is of great importance. Among the various properties of CNT, the most worrying in toxicological terms is its great insolubility. The insolubility in aqueous medium is one of the factors that decrease the biocompatibility, reducing cell viability in vitro. Functionalization techniques of nanostructures can be used to increase the solubility of CNT, thus increasing their biological compatibility. The objective of this work was to investigate the cytotoxicity caused by nonfunctionalized and functionalized multiple-walled carbon nanotubes (MWCNT) through a chemical method and subsequent purification. For the in vitro tests, the treated cells (RAW 264.7 and VERO cells) were cultured with various concentrations of CNT described in the literature for comparison (5, 10, 25, 50 and 100 μg / ml). Cells from the control group with culture medium were cultured with DMEM culture medium supplemented with 10% fetal bovine serum (FBS), and the positive control for cell damage with 100 mM of hydrogen peroxide. Cells remained in treatments for the 24 hour periods. Cell viability was then determined by the tripan blue exclusion method, which remained around 70%. Biochemical tests for cytotoxicity were carried out by the release of the enzyme lactate dehydrogenase (LDH) in the cell supernatant, nitric oxide in the macrophages, MTT, and a cell count of the supernatant after treatment. The results showed no significant difference in cytotoxicity of the samples, so the experiment was repeated using a VERO cell line, and concentrations were increased (100, 250, 500, 1000 and 5000 μg / ml). The MTT, LDH, neutral red and tripan blue counts were again performed. This second result demonstrated that functionalization decreases the cytotoxic effect of the MWCNT used. The methodology used was easy to apply and could be used for future analyzes of cytotoxicity using these nanomaterials.